2018
DOI: 10.1111/hae.13441
|View full text |Cite
|
Sign up to set email alerts
|

Movement behaviour in adults with haemophilia compared to healthy adults

Abstract: Movement behaviour of adults with severe haemophilia differs from healthy adults, mainly due to less walking and less running. No differences were found in other activities and postures or the distribution of movement behaviour over the day. No significant differences were found between adults with mild/moderate haemophilia and healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
(51 reference statements)
6
21
0
Order By: Relevance
“…Physical activity behaviour of children and adolescent PWH was found to be at least equally active than that of healthy controls 14,15 . In contrast, a study that objectively assessed the physical activity of adult PWH concluded that the movement behaviour of adults with severe haemophilia differs from healthy adults, mainly due to less walking and less running 16 . To our knowledge, no objective measurement of time spent in different intensities of physical activity in adult PWH has been carried out to date.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Physical activity behaviour of children and adolescent PWH was found to be at least equally active than that of healthy controls 14,15 . In contrast, a study that objectively assessed the physical activity of adult PWH concluded that the movement behaviour of adults with severe haemophilia differs from healthy adults, mainly due to less walking and less running 16 . To our knowledge, no objective measurement of time spent in different intensities of physical activity in adult PWH has been carried out to date.…”
Section: Introductionmentioning
confidence: 80%
“…14,15 In contrast, a study that objectively assessed the physical activity of adult PWH concluded that the movement behaviour of adults with severe haemophilia differs from healthy adults, mainly due to less walking and less running. 16 To our knowledge, no objective measurement of time spent in different intensities of physical activity in adult PWH has been carried out to date. Generally, a minimum of 150 min of moderate or 75 min of vigorous-intensity physical activity (or a combination of both) per week is recommended for adults to improve cardiorespiratory and muscular fitness, bone health and reduce the risk of non-communicable diseases and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research already showed that PWH are less physically active than healthy adults, but show similar sedentary behaviour. 3 Furthermore, previous studies indicated that PA level is explained only in small part by joint health. 11 This is supported by the findings in the current study, which show that only persons with a ‘bikers and runners’ movement pattern have a better joint health, but that joint health of PWH with a ‘walkers’ or ‘sedentary’ movement pattern is comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, adults with severe haemophilia are less physically active than healthy adults. 3 In patients with osteoarthritis (OA) avoidance of activities and more sedentary time induce a negative vicious circle of disuse, loss of muscle mass, reduced joint stability, proprioception and postural control and increased limitations in activities. 4 Given the similarities in pathogenesis of HA and OA, similar effects in persons with haemophilia (PWH) can be postulated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have employed research-grade accelerometers (ActiGraph GT3X, ActiTrac, etc.) to objectively monitor the amount and intensity of PA [26,27,28,29], but despite being widely used in biomedical research, commercial activity monitors in PWH have been used only in a few works. Using pedometers, Goto et al reported the number of steps/day in a case report [30] and in a cohort of 16 patients included in a self-monitoring program [31], and Pérez-Alenda et al quantified the daily PA in seven patients using a Fitbit wristband [32].…”
Section: Introductionmentioning
confidence: 99%